Binding thermodynamics discriminates fragments from druglike compounds: a thermodynamic description of fragment-based drug discovery. Issue 4 (April 2017) - Williams, Glyn; Ferenczy, György G.; Ulander, Johan; Keserű, György M.
Highlights: A large binding thermodynamics dataset of 1364 complexes has been analysed. Unlike many drug-like compounds, fragments bind enthalpically to their protein targets. It suggests a thermodynamic rationale for prioritising compounds forming specific key interactions. Abstract : Small is beautiful – reducing the size and complexity of chemical starting points for drug design allows better sampling of chemical space, reveals the most energetically important interactions within protein-binding sites and can lead to improvements in the physicochemical properties of the final drug. The impact of fragment-based drug discovery (FBDD) on recent drug discovery projects and our improved knowledge of the structural and thermodynamic details of ligand binding has prompted us to explore the relationships between ligand-binding thermodynamics and FBDD. Information on binding thermodynamics can give insights into the contributions to protein–ligand interactions and could therefore be used to prioritise compounds with a high degree of specificity in forming key interactions. Abstract : A large thermodynamic dataset from Astex, AstraZeneca, Pfizer and academic labs that includes fragment–protein interactions demonstrates that, when compared with many traditional druglike compounds, fragments bind more enthalpically to their protein targets.